Evaluating The Satisfaction of Passengers Towards Metro Rail Services- Bangladesh Perspective (Global Journal of Management and Business Research, 2024)
Bangladesh has launched the mass rapid transit MRT service for the first time in the transportation sector The MRT has significantly brought access to instantaneous communication in one of the congested cities Dhaka Since the service is a brand-new offering in Bangladesh there is a complete gap in research in this sector Therefore the objective of this study is to evaluate the effects of service quality dimensions on passengers satisfaction with MRT in Bangladesh The researchers used a convenient sampling method and collected primary data from 251 respondents who consumed the MRT service frequently Using the reliable software Smart PLS 3 0 the data were analyzed The researchers have examined Cronbach s alpha composite reliability and average variance extracted AVE to test the reliability and validity of the collected data This study finds that the constructs namely tangibility responsiveness assurance hedonic motivation and price value are significant in determining passengers satisfaction with MRT Price value is more significant followed by hedonic motivation and responsiveness In contrast statistics reveal that reliability and empathy are insignificant in nature
Keywords: passengers’ satisfaction; metro rail service; service quality dimensions; bangladesh